New species of Mycena (Mycenaceae, Agaricales) with colored lamellae and three new species records from China - Na, Qin; Bau, Tolgor (Phytotaxa, 2018)
Four species of Mycena possessing a colored lamellar are reported. Of these, Mycena entolomoides is described as new and is distinguished by an incarnate color of the whole lamellae, and M. citrinomarginata, M. purpureofusca, and M. strobilinoidea are recorded for the first time in China. A complete description, drawings and photographs of the morphological characters of M. entolomoides sp. nov. are accompanied by comparisons with closely related taxa. The three species newly recorded in China are considered in agreement with those species in Europe and North America. Phylogenetic analysis based on ITS sequences showed that M. entolomoides sp. nov. forms a monophyletic clade, well supported by maximum likelihood and Bayesian inference.